Media networks : architectures, applications, and standards - Moustafa, Hassnaa.; Zeadally, Sherali. (Taylor & Francis, 2012)
"With a focus on video and audio-visual services, this book considers different media network architectures along with related protocols and standards. It presents different digital TV technologies along with their deployment architectures, discussing promising media content delivery architectures, including Future Internet, Content Delivery Networks, and Content Centric Networks. The author addresses related technical challenges and standardization efforts. Chapters cover the management of media information and immersive technologies that account for advanced services personalization, immersive technologies architectures and applications, e-health, and e-learning"--